Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) - Klein, Joana Tartari; Barcellos, Aline; Grazia, Jocélia; Redaelli, Luiza Rodrigues (Zootaxa, 2012)
A new species of Dichelops (Dichelops) Spinola is described, based upon morphological characters. D. (D.) australis sp.nov. is compared with D. (D.) bicolor Distant, D. (D.) avilapiresi Grazia, and D. (D.) pradoi Grazia. Comparative illustrations of external genitalia are provided. A revised key to separate the species of the subgenus Dichelops is also presented.